Evaluation of Prison-Based Drug Treatment in Pennsylvania, 2000-2001 - Welsh, Wayne N. ([Verlag nicht ermittelbar], 2003)
The purpose of this study was to examine multiple treatment process measures and post-release outcomes for inmates who participated in Therapeutic Community (TC) drug treatment programs or comparison groups provided by the Pennsylvania Department of Corrections at five state prisons. The project attempted to examine more closely the relationships among inmate characteristics, treatment process, and treatment outcomes than previous studies in order to explore critical issues in prison-based drug treatment programming and policies. Researchers examined in-treatment measures and multiple post-release outcomes for inmates who participated in TC drug treatment programs or comparison groups at five state prisons: Graterford, Houtzdale, Cresson, Waymart, and Huntingdon. Matched comparison groups were made up of TC-eligible inmates who participated in less intensive forms of treatment (e.g., short-term drug education and outpatient treatment groups) due to a shortage of intensive treatment slots at the five institutions. Included in the treatment sample were all current TC residents as of January 1, 2000. New subjects were added to the study as they were admitted to treatment programs. Between January 1 and November 30, 2000, data on all inmates admitted to or discharged from alcohol or drug treatment programs were collected on a monthly basis. Monthly tracking was continued throughout the study to determine treatment outcomes (e.g., successful vs. unsuccessful). TC clients were asked to complete additional self-report measures that tapped psychological constructs and inmate perceptions of the treatment experience, and TC counselors were asked to complete periodic reassessments of each inmate's participation in treatment. Self-reports of treatment process and psychological functioning were gathered within 30 days after admission, again after six months, again at the end of 12 months, and again at discharge if the inmate remained in TC longer than 12 months. Counselor ratings of inmate participation in treatment were similarly gathered one month, six months, and 12 months following admission to treatment. After release, both treatment and comparison groups were tracked over time to monitor rearrest, reincarceration, drug use, and employment. Measures can be broken down into the following four categories and their sources: (1) Inmate Background Factors were collected from the Pennsylvania Additive Classification System (PACT), the Pennsylvania Department of Corrections Screening Instrument (PACSI), and the TCU (Texas Christian University) Drug Screen. (2) Institutional Indicators: Impacts Internal to the Prison Environment were collected from the Department of Corrections Misconduct Database, research and program records, and TCU Resident Evaluation of Self and Treatment (REST) forms. (3) Intermediate or "Proximal" Outcomes: Reductions in Risk for Drug Use and Criminal Behavior were collected from research and program records, TCU Counselor Rating of Client (CRC) forms, and TCU Resident Evaluation of Self and Treatment (REST) forms. (4) Post-Release Indicators: Inmate Behavior Upon Release from Prison were collected from the Pennsylvania Board of Probation and Parole, Pennsylvania state police records provided by the Pennsylvania Commission on Crime and Delinquency (PCCD), and the Department of Corrections inmate records system.